Production and Characterization of Bacillus firmus pectinase - Anna Roosdiana; Sasangka Prasetyawan; Chanif Mahdi; Sutrisno Sutrisno (The Journal of Pure and Applied Chemistry Research, 2013)
Pectinase is enzyme which functions to hydrolyze pectin become D-galacturonic acid unit. This enzyme is potential in various industries, especially in fruit juice industry.  Pectinase can be derived from various microorganisms resulting in different pectinase character. The aims of this research were to determine the optimum condition of pectinase production and to characterize the resulted pectinase including optimum condition of pectinase activity and the influence of metal ion.  The optimum condition of pectinase production was carried out by growing Bacillus firmus on basal media containing pectin as inducer at various  pH (5, 6, 7, 8, 9, 10), temperature (30, 35, 40, 45, 50) oC and fermentation time (6, 12, 18, 24, 30, 36) hours. while the optimum pectinase activity was done at various pH ( 4, 6, 7, 8, 10 ), temperature (30, 35, 40, 45, 50) oC and reaction time (10, 20, 30, 40, 50) minutes. The influence of Zn2+, Mg2+, K+ at 2-10 mM to pectinase activity were also investigated. The result showed that optimum condition of pectinase production occurred at pH7-8, temperature 40-50 oC and fermentation time 18hours, while the optimum condition of pectinase activity was pH 7, temperature 50 oC and reaction time 30 minutes. The existence of Zn2+, Mg2+, K+ ions  affected significantly to pectinase activity.  Mg2+ acted as non competitive inhibitor; however K+ and Zn2+ acted as un competitive inhibitor.